.PROFIL.PENGGUNAAN.OBAT.BATUK.PILEK.PADA.ANAK. SECARA SWAMEDIKASI DI APOTEK SYIFA FARMA MAKASSAR - Muhammad Tahir; Zakiah Thahir (Akademi Farmasi Yamasi Makassar, 2022)
The development of the disease encourages people to look for alternatives to self-medication or self-medication that is therapeutically effective but efficient in terms of cost, one of which is the use of over-the-Counter cough and cold medicines given to children. Dosing for the use of OTC cold cough medicines is set based on adult doses and has not been fully tested for effectiveness in children, allowing the use of inappropriate drugs. This research aims to.knowing the profile of the use of cough and cold medicines in children by self-medication at Syifa Farma pharmacy. This study is descriptive with interview techniques using questionnaires to all parents who want to use cold cough medicine in children in the period June 2021. The results obtained 65 respondents of the study, the majority of children suffering from cold cough is 2-6 years (67.69%), (47.69%) parents directly give over-the-counter cold cough medicine by reason of treatment swamedikan disease symptoms are still mild(52.632%), the use of most drugs is hufagrif flu&cough (29.23%) and pimtrakol (26.15%) and the most side effects are drowsiness (72.31%).